2013
DOI: 10.1177/1470320313481255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of taurine supplementation on blood pressure in gestational protein-restricted offspring: Effect on the medial solitary tract nucleus cell numbers, angiotensin receptors, and renal sodium handling

Abstract: Objective: The current study considers changes of the postnatal brainstem cell number and angiotensin receptors by maternal protein restriction (LP) and LP taurine supplementation (LPT), and its impact on arterial hypertension development in adult life. Methods and results: The brain tissue studies were performed by immunoblotting, immunohistochemistry, and isotropic fractionator analysis. The current study shows that elevated blood pressure associated with decreased fractional urinary sodium excretion (FE Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
2
11
0
2
Order By: Relevance
“…Also, the renal pelvis of LP rats did not strongly express CGRP when compared with NP rats, whereas no change was observed in SP immunostaining. These data were found in adult male LP offspring, accompanied by marked, early, and sustained (beyond 7 weeks of life) raised arterial pressure and a substantial renal decrease of urinary sodium excretion with unchanged creatinine clearance and usually filtered sodium (Mesquita et al, 2010a,b;de Lima et al, 2013;Sene et al, 2013;Scabora et al, 2015;Custódio et al, 2017;Cardoso et al, 2019). Also, a reduction in potassium excretion in LP offspring in the same studies suggest reabsorption of sodium, which may occur before distal nephron segments.…”
Section: Effects Of Gestational Protein Restriction On Renal Sympathetic Nerve Activitymentioning
confidence: 77%
“…Also, the renal pelvis of LP rats did not strongly express CGRP when compared with NP rats, whereas no change was observed in SP immunostaining. These data were found in adult male LP offspring, accompanied by marked, early, and sustained (beyond 7 weeks of life) raised arterial pressure and a substantial renal decrease of urinary sodium excretion with unchanged creatinine clearance and usually filtered sodium (Mesquita et al, 2010a,b;de Lima et al, 2013;Sene et al, 2013;Scabora et al, 2015;Custódio et al, 2017;Cardoso et al, 2019). Also, a reduction in potassium excretion in LP offspring in the same studies suggest reabsorption of sodium, which may occur before distal nephron segments.…”
Section: Effects Of Gestational Protein Restriction On Renal Sympathetic Nerve Activitymentioning
confidence: 77%
“…Among those diet components, taurine (Scabora et al. ) and folic acid (Torrens et al. ) supplemented to LP dams have been shown to rescue the adult offspring from developing hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, taurine‐rich food is easily consumed daily. Some studies suggested that taurine has a programming effect on hypertension . The purpose of the present study was to determine whether taurine administration during pregnancy and lactation would influence (a) systolic blood pressure (SBP), (b) aortic geometry, and (c) cardiac hypertrophy in adult (22 weeks old [wo]) SHR.…”
Section: Introductionmentioning
confidence: 99%